CD30 associates with EBER-EBV but not HCV-NS3 in T-cell non-Hodgkin lymphoma - Juwita, Rizki Amalia; Saputra, Lili Ananta; Fiilasari, Ika; Hardianti, Mardiah Suci; Anggorowati, Nungki (Frontiers in Virology, 2025)
IntroductionT-cell lymphoma contributes to malignancy worldwide, and the prognosis of this cancer is related to CD30 expression. Some T-cell lymphomas, including extranodal NK/T-cell lymphoma (ENKTCL), an aggressive lymphoma, have been commonly associated with Epstein-Barr virus (EBV) infection. EBV can be detected using Epstein-Barr-encoded RNA (EBER) in situ hybridization (ISH). In addition, hepatitis C virus (HCV) infection also has a role in the occurrence of non-Hodgkin Lymphoma (NHL). A nonstructural protein of the HCV, NS3, may be involved in lymphoma development. Furthermore, the Epstein-Barr virus has also long been associated with CD30. However, the relationship between CD30 and NS3 was unknown. This research aims to study the relationship between CD30, NS3, and EBER in T-cell lymphoma.MethodsData and paraffin blocks were collected from NHL T-cell patients, and 30 samples were chosen for the study after meeting the criteria. The paraffin block was stained with CD30, NS3, and EBER immunohistochemistry and read by two pathologists.ResultsFrom 30 cases, the dominant subtype expressing CD30 was Extranodal Natural Killer T-cell Lymphoma (ENKTCL) (84.62%). In total, 20 (66.7%) samples expressed CD30, 6 (20%) expressed NS3, and 18 (60%) samples expressed EBER. There is no significant relationship between NS3 and EBER. Meanwhile, CD30 expression correlated statistically with EBER (P = 0.001).DiscussionCD30 expression in T-cell non-Hodgkin lymphoma was not significantly associated with clinicopathology data in this study. CD30, NS3, and EBER were expressed in T-cell non-Hodgkin lymphoma. There exists a relationship between CD30 and EBER, but this study revealed no relationship between NS3 and EBER expression.